Study on Creating a Local Branding Process to Increase the Attractiveness of the Area - Mădălina ȘERBAN; Maria-Magdalena TUREK-RAHOVEANU; Luxița Risnoveanu; Cristian Silviu Simionescu (Communications of International Proceedings, 2020)
This article aims to present a methodology to analyze how the image of an area is affected by different branding strategies at the level of entrepreneurs. The first methodology aims to stimulate a brand process in which there are sufficient opportunities for an open debate in the process of developing and implementing a local brand. The second methodology refers to the stimulation of an identity-image match in which the image of the place communicates and reflects the identity of the place. It is assumed that each strategy has a positive effect, the reputation of the place, as well as the immediate positive effects by increasing the adoption of the place brand. The research will be applied structurally by modeling the equation to the data from the local surveys from Podgoria Dealul Mare, in Romania among the professionals working in the field of marketing and branding. The results will follow if the branding of the area will have direct (positive) effects on the reputation of the place. The indirect effect on the reputation of the site mediated by the adoption of the site brand reduces conflicts between stakeholders. The theoretical and managerial implications are discussed.
Keywords: branding; rural areas; sustainable tourism; the attractiveness of the area.